Racism - Memmi, Albert (University of Minnesota Press, 2000)
"Racism: It is social, not "natural"; it is general, not "personal"; and it is tragically effective. In a remarkable meditation on a subject at the troubled center of American life, Albert Memmi investigates racism as social pathology--a cultural disease that prevails because it allows one segment of society to empower itself at the expense of another. By turns historical, sociological, and autobiographical, Racism moves beyond individual prejudice and taste to engage the broader questions of collective behavior and social responsibility"--Publisher's description